Insights into prognosis and immune infiltration of cuproptosis-related genes in breast cancer - Huang, Tingting; Liu, Yankuo; Li, Jiwei; Shi, Bingbing; Shan, Zhengda; Shi, Zhiyuan; Yang, Zhangru (Frontiers in Immunology, 2022)
Breast cancer (BC) has been ranking first in incidence and the leading cause of death among female cancers worldwide based on the latest report. Regulated cell death (RCD) plays a significant role in tumor initiation and provides an important target of cancer treatment. Cuproptosis, a novel form of RCD, is ignited by mitochondrial stress, particularly the lipoylated mitochondrial enzymes aggregation. However, the role of cuproptosis-related genes (CRGs) in tumor generation and progression remains unclear. In the present study, we utilized a variety of bioinformatics methods to explore the role of CRGs expression in tumor prognosis and immunity response. Our results indicated that CRGs expression is different in BC and normal breast tissues. Then we conducted the survival and cox regression analysis of these genes and found that upregulated PDHA1 expression was associated with worse endpoint of BC. Moreover, we also performed immune infiltration analysis of CRGs, and the result demonstrated that PDHA1 expression was closely related to the infiltration level of CD4+ memory T cell, macrophage M0 and M1 cell and mast cell in BC. Therefore, PDHA1 can be an independent prognostic biomarker and potential target for immunotherapy of BC.